2017
DOI: 10.5152/tpd.2017.5066
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of IgG and IgM anti-Toxoplasma gondii Antibodies in Blood Donors at Urmia Blood Transfusion Organization, Iran

Abstract: Objective: The importance of toxoplasmosis lies in its global spread, opportunistic nature, and causative role in abortion or irreparable adverse effects on infants of infected pregnant women. Toxoplasma gondii has different transmission routes to humans, including blood transfusion. The objective of the present study was to evaluate the prevalence of IgG and IgM antibodies specific for T. gondii in blood donors at the Urmia Blood Transfusion Organization in west Azerbaijan, Iran. Methods: The present analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Consistent with the literature, this study showed that blood donors had the infection in the past, which may be occurred at a younger age [19][20][21]. It is well known that a hallmark of toxoplasmosis is that the parasite persists for months to years or even a lifetime in tissues.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with the literature, this study showed that blood donors had the infection in the past, which may be occurred at a younger age [19][20][21]. It is well known that a hallmark of toxoplasmosis is that the parasite persists for months to years or even a lifetime in tissues.…”
Section: Discussionsupporting
confidence: 86%
“…Included studies were performed in 12 provinces in Iran (Khorasan Razavi, Tehran, Kerman, Fars, Mazandaran, West Azerbaijan, Sistan and Baluchistan, Hamadan, Kohgiluyeh and Boyer-Ahmad, Chaharmahal and Bakhtiari, Khuzestan, and Ardabil), and most studies were done in Khorasan Razavi and Fars (n = 3 per province), as well as Tehran, Kerman, and Mazandaran (n = 2 per province). Among 19 included studies [ [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] ], 8226 apparently healthy blood donors were tested regarding T. gondii -specific IgG and/or IgM antibodies, among which 32.9% (95% CI: 25.3%–41.6%) were seropositive only for IgG, 1.4% (95% CI: 0.9%–2.1%) were seropositive only for IgM, and 1.7% (95% CI: 1.3%–2.1%) were positive for both IgG and IgM antibodies ( Fig. 2 A–C).…”
Section: Resultsmentioning
confidence: 99%
“…of blood donors No. seropositive for T. gondii Pooled seroprevalence (95% CI) OR (95% CI) P -value Heterogeneity I 2 (%) References Gender Male 11 5162 1821 38.8 (28.6–50.0) 1 [ 26 , [31] , [32] , [33] , [36] , [37] , [38] , 40 , [42] , [43] , [44] ] Female 451 230 54.5 (42.6–65.9) 1.98 (1.52–2.58) < 0.001 23.7 Residence Urban 8 2479 976 38.3 (27.7–50.1) 1 [ 33 , 36 , [38] , [39] , [40] , [42] , [43] , [44] ] Rural 1044 500 45.4 (30.2–61.5) 1.37 (0.97–1.93) 0.069 73.8 Blood group A 9 1467 510 …”
Section: Resultsmentioning
confidence: 99%